Rare phylotypes in stone, stool, and urine microbiomes are associated with urinary stone disease - Suryavanshi, Mangesh; Agudelo, Jose; Miller, Aaron (Frontiers in Molecular Biosciences, 2023)
In complex microbial communities, the importance of microbial species at very low abundance and prevalence for overall community structure and function, is increasingly being recognized. Clinical microbiome studies with urinary stone disease (USD) have indicated that both the gut and urinary tract microbiota are associated with the onset of the disease and that kidney stones themselves harbor a complex, but consistent and viable microbiome. However, it is unclear how rare phylotypes contribute to this association. Delineating the contribution of rare and common phylotypes to urinary stone disease is important for the development of bacteriotherapies to promote urologic health. As such, the objectives of the current report were to conduct a meta-analysis of 16S rRNA datasets derived from kidney stones, stool, and urine of participants with or without urinary stone disease. Consistent with past analyses, we found that the gut, upper urinary, and lower urinary tract microbiomes were all unique. Rare phylotypes comprised the majority of species observed in all sample types, with kidney stones exhibiting the greatest bias towards rarity, followed by urine and stool. Both the rare and common fractions contributed significantly to differences seen between sample types and by health disparity. Furthermore, the rare and common fractions were taxonomically unique across all sample types. A total of 222, and 320 unique rare phylotypes form urine and stool were found to be significantly associated to USD. A co-occurrence correlation analysis revealed that rare phylotypes are most important for microbiome structure in stones, followed by urine, then stool. Collectively, results indicate that rare phylotypes may be important for the pathophysiology of USD, particularly in the kidney stone matrix, which is inherently a very low microbial biomass niche, which can have implications for the diagnosis and treatment of kidney stones. Further studies are needed to investigate the functional significance of rare phylotypes in kidney stone pathogenesis.